2021
DOI: 10.1111/jscm.12259
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of Association and Collective Bargaining in Global Supply Chains: A Research Agenda

Abstract: This article outlines a research agenda for Freedom of Association and Collective Bargaining, two fundamental labor rights essential to the achievement of “Decent Work” for workers in global supply chains. The authors argue that SCM scholars are uniquely positioned to address how workers’ freedom of association and collective bargaining rights in global supply chains could be improved. This stems, in part, from the fact that SCM researchers and industry practitioners share a common “logic of efficiency” in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Subjective features relate to individual‐level research and job characteristics, while objective features are related to company‐level research (Petriglieri et al, 2019). The OM literature has traditionally focused on nonstandard forms of work, such as temporary contracts, but has not tended to investigate precarious work in relation to inadequate income and a lack of rights and protections (Kuruvilla & Li, 2021; Ojala & Pyiöriä, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Subjective features relate to individual‐level research and job characteristics, while objective features are related to company‐level research (Petriglieri et al, 2019). The OM literature has traditionally focused on nonstandard forms of work, such as temporary contracts, but has not tended to investigate precarious work in relation to inadequate income and a lack of rights and protections (Kuruvilla & Li, 2021; Ojala & Pyiöriä, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…We strive to expand labor rights to build economic and political development on a firmer social foundation. Democratic worker representation, collective bargaining and effective dispute resolution are key elements (Anner, 2012; Appelbaum and Lichtenstein, 2016; Kuruvilla and Li, 2021). From a gender perspective, sexual harassment and various types of inequality in job assignment and performance assessment – which are often grossly neglected – need to be monitored and overcome (Chan et al, 2020: 123–125).…”
Section: Discussionmentioning
confidence: 99%
“…While earlier studies concluded that CoCs can effectively alter firm behavior (Erwin, 2011;Somers, 2001), more recent studies have questioned such generalizations (Kuruvilla and Li, 2021;LeBaron, 2021). The effectiveness of CoC is likely dependent on factors such as the quality, implementation and management of the code (Babri et al, 2021;Cowton and Thompson, 2000;Jiang, 2009;Kuruvilla and Li, 2021;LeBaron, 2021). Nitsch et al (2005) argued that the degree of effectiveness depends on whether wrongdoings are exposed and sanctioned.…”
Section: The Implications Of Codes Of Conduct On Supplier Selection D...mentioning
confidence: 99%
“…Many companies have implemented Codes of Conduct (CoCs) to prevent working with unethical suppliers, but there are serious doubts about their effectiveness (e.g. Babri et al, 2021;Cowton and Thompson, 2000;Jiang, 2009;Kuruvilla and Li, 2021;LeBaron, 2021). Notably, Goebel et al (2018) found that the presence and distribution of a CoC within an organization does not inherently lead to an increased willingness among purchasing managers to pay a price premium for sustainability.…”
Section: Introductionmentioning
confidence: 99%